A comparison of mycolic acid analysis for nontuberculous mycobacteria identification by thin-layer chromatography and molecular methods - Fujimura Leite, Clarisse Queico [UNESP]; Da Silva Rocha, Adalgiza; De Andrade Leite, Sergio Roberto [UNESP]; Carvalho Ferreira, Rosa Maria; Suffys, Philip N.; Fonseca, Lella de Souza; Féres Saad, Maria Helena (Wiley, 2005)
The development of fast, inexpensive, and reliable tests to identify nontuberculous mycobacteria (NTM) is needed. Studies have indicated that the conventional identification procedures, including biochemical assays, are imprecise. This study evaluated a proposed alternative identification method in which 83 NTM isolates, previously identified by conventional biochemical testing and in-house M. avium IS1245-PCR amplification, were submitted to the following tests: thin-layer chromatography (TLC) of mycolic acids and PCR-restriction enzyme analysis of hsp65 (PRA). High-performance liquid chromatography (HPLC) analysis of mycolic acids and Southern blot analysis for M. avium IS1245 were performed on the strains that evidenced discrepancies on either of the above tests. Sixty-eight out of 83 (82%) isolates were concordantly identified by the presence of IS1245 and PRA and by TLC mycolic acid analysis. Discrepant results were found between the phenotypic and molecular tests in 12/83 (14.4%) isolates. Most of these strains were isolated from non-sterile body sites and were most probably colonizing in the host tissue. While TLC patterns suggested the presence of polymycobacterial infection in 3/83 (3.6%) cultures, this was the case in only one HPLC-tested culture and in none of those tested by PRA. The results of this study indicated that, as a phenotypic identification procedure, TLC mycolic acid determination could be considered a relatively simple and cost-effective method for routine screening of NTM isolates in mycobacteriology laboratory practice with a potential for use in developing countries. Further positive evidence was that this method demonstrated general agreement on MAC and M. simiae identification, including in the mixed cultures that predominated in the isolates of the disseminated infections in the AIDS patients under study. In view of the fact that the same treatment regimen is recommended for infections caused by these two species, TLC mycolic acid analysis may be a useful identification tool wherever molecular methods are unaffordable.
Keywords: IS1245; Mycolic acids; Nontuberculous mycobacteria; PRA; TLC; heat shock protein 65; mycolic acid; acquired immune deficiency syndrome; atypical Mycobacterium; bacterial colonization; bacterial strain; bacterium culture; bacterium detection; bacterium identification; bacterium isolate; bacterium isolation; controlled study; cost effectiveness analysis; enzyme assay; high performance liquid chromatography; intermethod comparison; mixed cell culture; Mycobacterium avium; nonhuman; phenotype; polymerase chain reaction; restriction mapping; screening test; Southern blotting; superinfection; thin layer chromatography; Bacterial Typing Techniques; Chromatography, Thin Layer; DNA, Bacterial; Mycobacterium; Mycolic Acids; atypical mycobacterium; Bacteria (microorganisms); Corynebacterineae